Evaluation of Malaysian Isolates of Trichoderma Harzianum Rifai and Gliocladium Virens Miller, Giddens and Foster for the Biological Control of Sclerotium Foot Rot of Chilli - Jomduang, Jinantana (1995)
Sclerotium foot rot of chilli (Capsicum annuum L.) caused by Sclerotium rolfsii Sacc. is commonly found to cause damage in almost all the chilli growing areas in Malaysia. Conventional methods to control the disease, for example, fungicide drenching and crop rotation, seem to be uneconomical and impractical. Recent years, integrated pest management strategy is being adopted for plant disease control which reduces or have lesser impact on the environment. The present study was carried out to evaluate the Malaysian isolates of Trichoderma harzianum Rifai and Gliocladium virens Miller, Giddens and Foster as biocontrol agents for Sclerotium foot rot of chilli both in glasshouse and small scale field trials. Infection mechanism of S. rolfsii on chilli plants and the antagonistic effects of T. harzianum and G. virens on S. rolfsii were also studied.